Characterization method for energy density and response speed of phase change energy storage composite material
Through experimental testing and finite element simulation, the energy density and response speed of phase change materials are characterized, and the problem of lack of standardized characterization methods in the existing technology is solved, and effective trade-offs and optimization of the performance of phase change materials are achieved to meet fast charging and fast release The demand for heat storage scenarios.
Patent Information
- Application Number
- CN202411254896.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing technology lacks standardized methods to characterize the energy density and response speed of phase change materials, resulting in the inability to effectively weigh these performance indicators when improving phase change materials, especially when meeting the needs of fast charging and fast heat storage scenarios. Slower problem.
Provide a method for characterizing the energy density and response speed of phase-change energy storage composite materials. By making standard samples, conducting experimental tests and finite element simulation, establishing the thermal coupling relationship between temperature field-solid-liquid phase changes, and calculating the energy density and response velocity and draw a ragon diagram to compare the performance differences between different materials.
Provide unified testing standards for different phase change materials, clarify the trade-off between their energy density and response speed, simplify testing operations, improve the reliability of results and theoretical credibility, and provide a reference path for optimization and improvement.
Smart Images

Figure CN119125221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of phase change material energy storage and response speed characterization, and particularly relates to a method for characterizing the energy density and response speed of a phase change energy storage composite material. Background Art
[0002] Phase change materials, as a special thermal management functional material, can change their own material state while keeping the temperature unchanged, and absorb or release a large amount of heat in this process, which is called latent heat. At the same time, the process of change in physical properties is called phase change process. The phase change process involves many factors, including the overall volume of the phase change material, ambient temperature, intrinsic thermal conductivity, impurity content and auxiliary materials, which will directly affect the latent heat storage or total time of the phase change process. The duration of the phase change process or the speed at which the material undergoes phase change during the phase change process can also be characterized by the phase change response speed, which is used to describe the speed of the entire phase change process.
[0003] The key properties of any energy storage device or material are its energy storage capacity and power characteristics. These properties were first compared and used through the Lagone diagram commonly used in electrochemical energy storage research. The Lagone diagram is a data graph with response speed (charging and discharging power) as the horizontal axis and energy density (energy storage capacity) as the vertical axis. The specific power is compared with the corresponding specific energy to quantitatively characterize the trade-off between the material's energy storage capacity and power density. Power density often plays a decisive role in the maximum achievable energy storage capacity. Phase change materials are one of the current mainstream energy storage and heat storage materials. Their energy density and response speed have always been performance indicators valued by researchers, but there is no standardized characterization method and comparison scheme so far.
[0004] For energy storage systems or energy storage materials, all of their characteristics have one thing in common, that is, different working output (input) powers often correspond to different amounts of released (stored) energy. Usually, faster response speeds result in smaller capacities, because faster response speeds often lead to greater transmission impedance, which increases energy loss during transmission. As a result, the total amount that can be stored or released is reduced. Conversely, slower response speeds correspond to larger total capacities.
[0005] With the research and invention of more and more types of phase change materials, a large number of phase change materials used in different scenarios are in urgent need of improvement. For example, phase change materials often face the problem of slow response speed due to their low thermal conductivity and cannot meet the needs of some fast charging and discharging heat storage scenarios. Therefore, the improvement research of materials is also mainly focused on increasing this thermal conductivity, and this improvement is usually achieved by adding other thermal conductive fillers to the phase change material or using a matrix. Although these composite materials have faster response speeds, they will sacrifice the space occupied by energy storage phase change materials under the same volume, resulting in lower energy density. Therefore, how to balance the ratio of energy density and response speed is a problem that must be considered for the further development of phase change materials. Summary of the invention
[0006] The purpose of the present invention is to provide a method for characterizing the energy density and response speed of a phase change energy storage composite material. The Lagun diagram obtained by characterization can clearly compare the performance differences between different phase change material types and designs.
[0007] The present invention provides a method for characterizing the energy density and response speed of a phase-change energy storage composite material, comprising the following steps:
[0008] Step 1: The phase change material or composite phase change material to be tested is made into a standard sample, and an experimental test is carried out under uniform test conditions to obtain the temperature change curve and total heating time of the material sample;
[0009] Step 2: Based on the phase change temperature range of the phase change material and the relevant data obtained from the test, according to the working principle of the heat engine and the laws of thermodynamics, the thermal physical property parameters of the phase change material sample are calculated;
[0010] Step 3: Establish the thermomechanical coupling relationship between temperature field and solid-liquid phase change and the finite element model for heat transfer calculation, submit the simulation conditions for multi-physics field coupling, and complete the subsequent solution, post-processing and result analysis of the finite element;
[0011] Step 4: Obtain the energy density and response speed of the phase change material sample based on calculation and finite element simulation. On the basis of repeating steps 1 to 3, obtain the energy density corresponding to different response speeds. Use the large amount of data obtained to make a Lagun diagram to compare the trade-off between energy density and response speed of each phase change material system.
[0012] Furthermore, in step 1, the phase change material is made into a rectangular sample of a specified size, with a large surface area and a thin thickness, and basic information such as the mass, density, porosity and processing technology of the sample under test is recorded;
[0013] Furthermore, in step 1, the sample to be tested is tested in a constant temperature and heat preservation environment. Starting from the same initial temperature, the sample to be tested is heated by a heat transfer medium using different heating powers. Different heating powers correspond to different cut-off temperatures. The temperature change of the sample to be tested under different heating powers and the time to heat up to the cut-off temperature are recorded.
[0014] Furthermore, in step 2, according to the working principle of the heat engine and the thermodynamic formula, when the heat transfer medium is in contact with the high-temperature (heat source) and low-temperature (sample) substances at the same time, the regular formulas 1 and 2 are satisfied:
[0015] Formula 1:
[0016] Formula 2:
[0017] Among them, T H is the instantaneous maximum temperature of the heat transfer medium after being heated by the heat source, T L It is the instantaneous minimum temperature of the heat transfer medium after it absorbs heat from the sample being tested and before it is heated again. HC is the instantaneous temperature of the heat transfer medium when it contacts the sample being tested, T LC Q is the instantaneous temperature when the heat transfer medium and the sample are about to separate. HC Q is the heat carried by the heat transfer medium from the heat source to the sample under test. LC is the amount of heat carried by the heat transfer medium from the separation of the sample to the reheating, α is the heat transfer coefficient, n is the heat transfer index, and t is the duration of the whole process;
[0018] Furthermore, when the whole process satisfies linear heat transfer, n = 1, while for nonlinear heat transfer process, n = 5 / 4;
[0019] Furthermore, by integrating the calculation formula 1 and the calculation formula 2 with respect to the time t, we obtain the calculation formula 3 and the calculation formula 4:
[0020] Formula 3: Q HC =α(T H -T HC ) n t
[0021] Formula 4: Q LC =α(T LC -T L ) n t
[0022] Furthermore, because the test is carried out in a constant temperature and heat preservation environment, the heat transfer process of the heat transfer medium between the heat source and the sample under test can be approximately regarded as an isothermal adiabatic process. At the same time, the duration of the adiabatic process is also short. Therefore, the heat loss of the heat transfer medium during the transfer process can be ignored, which approximately meets the assumption of energy conservation in the test. According to the second law of thermodynamics, the heat transfer process of the heat transfer medium between the heat source and the sample under test follows Formula 5:
[0023] Formula 5:
[0024] Furthermore, since the heat transfer medium transfers heat when passing through the sample, T HC and T LC There will be a difference between them, which is the heat absorbed and stored by the sample during the whole process. According to the definition of energy density and response speed, the thermal physical parameters of the sample are deduced to obtain formula 6, formula 7, formula 8 and formula 9:
[0025] Formula 6:
[0026] Formula 7:
[0027] Formula 8:
[0028] Formula 9:
[0029] Wherein, P is the heat transfer power, which is also one of the characterization methods of response speed, η is the capacity utilization efficiency, which represents the utilization rate of the heat that the tested sample can absorb at this response speed relative to the theoretical total heat storage, E is the total energy storage that the tested sample can achieve at this response speed, Es is the energy density related to mass, and m is the mass of the tested sample;
[0030] Furthermore, in step 2, the optimal value of heat transfer power that satisfies both fast response speed and high energy density can be obtained. The optimal value means that within a unit time, the phase change energy storage response can be completed quickly, and at the same time, the energy density achieved at this response speed is the highest compared to the same level, which is the best performance of the trade-off between response speed and energy density. In order to obtain the optimal value, the temperature difference variable is set by formula 10 and formula 11:
[0031] Formula 10: x = T H -T HC
[0032] Formula 11: y = T LC -T L
[0033] The temperature difference variables x and y represent the temperature (heat) lost by the heat transfer medium during the transfer process. However, since the heat loss in the actual transfer process is extremely small and the transfer path is short and equal in length, it can be approximately regarded as x = y.
[0034] Furthermore, combining the second law of thermodynamics and the set condition x=y, Formula 5 can be derived to obtain Formula 12:
[0035] Formula 12:
[0036] Furthermore, according to the principle of combined ratio ratio, Formula 12 is transformed to obtain the derived Formula 13:
[0037] Formula 13:
[0038] Furthermore, according to the definition of response speed, the definition formula of heat transfer power is obtained as follows:
[0039] Formula 14:
[0040] Furthermore, considering Formula 14 as a function of P with respect to variable x, and considering other parameters as constants set in the test, the derivative of Formula 14 with respect to variable x can obtain Formula 15:
[0041] Formula 15:
[0042] Furthermore, since Formula 15 is The function of variable x, and n ≧ 1, so when the optimal value of heat transfer power that satisfies both fast response speed and high energy density is obtained, it should be taken At this point, the optimal value of x can be obtained max , thus we get the derivation formula 16:
[0043] Formula 16:
[0044] Furthermore, we get x max About T only H and T L Function, T H and T L It is a parameter that can be directly tested in the experiment. By controlling the output power of the heat source, T H and T L The optimal value is achieved by using the numerical conditions to obtain the optimal energy density and response speed under the optimal temperature difference. max Substituting into formula 6, formula 7, formula 8 and formula 9, the optimal temperature difference value x can be obtained. max The corresponding optimal response speed P max, maximum efficiency η max , optimal total energy E max and the optimal energy density Es max , as shown in the derivation of Formula 17, Formula 18, Formula 19 and Formula 20:
[0045] Formula 17:
[0046] Formula 18:
[0047] Formula 19:
[0048] Formula 20:
[0049] Furthermore, in step three, a temperature field-solid-liquid coupling model is established through finite element simulation software, three-dimensional geometric components of the same size and shape as the sample to be tested are assembled, and various thermophysical parameters of the phase change material or composite phase change material that change with temperature are set;
[0050] Furthermore, in step 3, boundary conditions, heating surfaces, initial temperatures and heat interaction conditions are added to the constructed three-dimensional geometric components, and the heat interaction is based on the temperature difference on both sides of the interface;
[0051] Furthermore, in step 3, a mesh is set for the constructed three-dimensional geometric component. Since it is a rectangular thin-walled model, a triangular distributed mesh can be selected to reduce the amount of calculation while ensuring the accuracy of the simulation results. The mesh can be refined at the corners and vertices of the model.
[0052] Furthermore, in step three, after setting various parameters in the finite element simulation software, a steady-state solution of the model is performed. By reading the information files such as the heat transfer coefficient, thermal conductivity and heat transfer path of the set material and combining the calculation of the thermodynamic formula, the real-time changes of the temperature, response speed and energy density at various locations of the phase change material model can be obtained. The obtained simulation results are compared with the actual test results. If the error rate is below 5%, the reliability of this test is proved.
[0053] Furthermore, in step 4, the same phase change material sample can be tested repeatedly for multiple times to test the energy density that the sample can achieve at different response speeds. Different response speeds can be set with a value range and a step-by-step value to reduce the overall testing workload. The response speed and energy density parameters obtained in each test are marked at the corresponding points in the Lagun diagram, and the trade-off relationship between energy density and response speed in the phase change material system can be obtained.
[0054] Compared with the prior art, the present invention has at least one of the following effects:
[0055] ① It provides a unified test standard for phase change materials or composite phase change materials of different systems, and provides a standardized evaluation and comparison scheme for phase change energy storage material systems with different material combinations, shape designs, auxiliary skeletons or process treatments. The test results and performance change trends can be clearly displayed in the Lagun diagram, which is intuitive, visual, and has strong reference value. The advantages and disadvantages are obvious, which can provide a good optimization idea for the subsequent improvement of different composite phase change material systems, and also preserve the data foundation for the future creation of a large database of energy density and response speed of composite phase change materials;
[0056] ② The test operation process is simple, the sample is easy to place and take, and the experimental test can be completed in a constant temperature and humidity room. The heat loss during the test is very small, and basically no serious test errors will be caused. The final test results can also be cross-referenced with the finite element simulation results, and the reliability is strong;
[0057] ③ The theoretical derivation formulas are all based on the basic thermodynamic formulas and the basic principles of heat engine operation. The sources of the physical parameters involved are clear, which greatly improves the theoretical credibility. The derivation process is scientific, logical, and highly relevant. According to the intrinsic thermophysical parameters of the tested samples and the test results, the relationship between the energy density and response speed of the phase change material system can be accurately calculated. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 A flow chart for characterizing the energy density and response speed of phase change materials provided for this application;
[0059] Figure 2 A three-dimensional simulation model of a phase change material sample in an embodiment of the present application and a schematic diagram of its mesh division;
[0060] Figure 3 This is a comparative relationship diagram of the energy density and response speed of the tested phase change material at different test cut-off temperatures (durations) in the embodiments of the present application;
[0061] Figure 4 This is a simulation result diagram of the solid-liquid phase volume ratio and temperature change curve of the phase change material sample in the test process in the embodiment of the present application;
[0062] Figure 5 Refer to the comparison chart of the temperature change of the heat transfer medium in the actual test process and the finite element simulation result at different response speeds in the embodiment of the present application;
[0063] Figure 6 1 is a Lagung diagram of energy density and response speed of each phase change material system in the embodiments of the present application. DETAILED DESCRIPTION
[0064] In order to further illustrate the present invention more clearly, the present invention is described in further detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0065] Embodiment 1
[0066] Select graphite paraffin composite phase change material as the test object, and make the material into a rectangular sample of specified size. The sample has a large surface area and a thin thickness. At the same time, record the basic information of the sample such as mass, density, porosity and processing technology. The complete test steps are as follows: Figure 1 shown.
[0067] The composite phase change material sample to be tested is tested in a constant temperature and heat preservation environment. The tested sample is first cooled to 0°C as a whole and maintained for 15 minutes to ensure that the initial temperature of each test is the same. Then, different heating powers are used to heat the tested sample through a heat transfer medium. At the same time, different heating powers correspond to different cut-off temperatures. In this embodiment, the tested sample is tested three times using heating powers of 0.58°C, 0.88°C and 1.05°C, respectively. The test cut-off temperatures corresponding to the three different heating powers are 9°C, 12°C and 15°C, respectively. The temperature changes of the tested samples under the three different heating powers and the time to heat up to each corresponding cut-off temperature are recorded respectively.
[0068] According to the working principle of heat engine and the derivation of thermodynamic formula, when the heat transfer medium is in contact with high temperature (heat source) and low temperature (sample) substances at the same time, the regular formulas 1 and 2 are satisfied:
[0069] Formula 1:
[0070] Formula 2:
[0071] Among them, T H is the instantaneous maximum temperature of the heat transfer medium after being heated by the heat source, T L It is the instantaneous minimum temperature of the heat transfer medium after it absorbs heat from the sample being tested and before it is heated again. HC is the instantaneous temperature of the heat transfer medium when it contacts the sample being tested, T LC Q is the instantaneous temperature when the heat transfer medium and the sample are about to separate. HC Q is the heat carried by the heat transfer medium from the heat source to the sample under test. LC is the heat carried by the heat transfer medium after it is separated from the sample and before it is heated again, α is the heat transfer coefficient, n is the heat transfer index, and t is the duration of the entire process. Because linear heat transfer is satisfied during the test of the graphite paraffin composite phase change material sample, n=1 can be taken.
[0072] Integrate the calculation formula 1 and formula 2 for the duration t to obtain the calculation formula 3 and formula 4:
[0073] Formula 3: Q HC =α(T H -T HC ) n t
[0074] Formula 4: Q LC =α(T LC -T L ) n t
[0075] Because the test is carried out in a constant temperature and heat preservation environment, the heat transfer process between the heat source and the sample under test can be approximately regarded as an isothermal adiabatic process. At the same time, the duration of the adiabatic process is also short. Therefore, the heat loss of the heat transfer medium during the transfer process can be ignored, which approximately meets the assumption of energy conservation in the test. According to the second law of thermodynamics, the heat transfer process between the heat source and the sample under test follows Formula 5:
[0076] Formula 5:
[0077] Since the heat transfer medium transfers heat when passing through the sample under test, there will be a difference between and . This difference is the heat absorbed and stored by the sample under test during the whole process. According to the definition of energy density and response speed, the various thermal physical property parameters of the sample under test are derived to obtain formula 6, formula 7, formula 8 and formula 9:
[0078] Formula 6:
[0079] Formula 7:
[0080] Formula 8:
[0081] Formula 9:
[0082] Among them, P is the heat transfer power, which is also one of the characterization methods of response speed. η is the capacity utilization efficiency, which represents the utilization rate of the heat that the measured sample can absorb at this response speed relative to the theoretical total heat storage. E is the total energy storage that the measured sample can achieve at this response speed. Es is the energy density related to mass, and m is the mass of the measured sample.
[0083] Furthermore, the optimal value of heat transfer power that satisfies both fast response speed and high energy density can be obtained. The optimal value means that within a unit time, the phase change energy storage response can be completed quickly, and at the same time, the energy density achieved at this response speed is the highest compared to the same level, which is the best performance of the trade-off between response speed and energy density. In order to obtain the optimal value, the temperature difference variable is set by formula 10 and formula 11:
[0084] Formula 10: x = T H -T HC
[0085] Formula 11: y = T LC -T L
[0086] The temperature difference variables x and y represent the temperature (heat) lost by the heat transfer medium during the transfer process. However, since the heat loss during the actual transfer process is extremely small and the transfer path is short and of equal length, it can be approximately regarded as x=y.
[0087] Combining the second law of thermodynamics and the set condition x=y, Formula 5 can be derived to obtain Formula 12:
[0088] Formula 12:
[0089] According to the principle of combined ratio, Formula 12 is transformed to obtain the derived Formula 13:
[0090] Formula 13:
[0091] According to the definition of response speed, the definition formula of heat transfer power is obtained as follows:
[0092] Formula 14:
[0093] Formula 14 is regarded as a function of P with respect to variable x, and other parameters are regarded as constants set in the test. By taking the derivative of formula 14 with respect to variable x, formula 15 can be obtained:
[0094] Formula 15:
[0095] Because formula 15 is The function of variable x, and n = 1, so when the optimal value of heat transfer power that satisfies both fast response speed and high energy density is obtained, it should be taken At this point, the optimal value of x can be obtained max , thus we get the derivation formula 16:
[0096] Formula 16:
[0097] In this way, the optimal energy density and response speed under the optimal temperature difference are obtained. max Substituting into formula 6, formula 7, formula 8 and formula 9, the optimal temperature difference value x can be obtained. max The corresponding optimal response speed P max , maximum efficiency η max , optimal total energy E max and the optimal energy density Es max , as shown in the derivation of Formula 17, Formula 18, Formula 19 and Formula 20:
[0098] Formula 17:
[0099] Formula 18:
[0100] Formula 19:
[0101] Formula 20:
[0102] Then, the temperature field-solid-liquid coupling model can be established through finite element simulation software, three-dimensional geometric components of the same size and shape as the sample being tested can be assembled, and various thermophysical parameters of the phase change material or composite phase change material that change with temperature can be set.
[0103] Furthermore, boundary conditions, heating surfaces, initial temperatures and heat interaction conditions are added to the constructed three-dimensional geometric components, and the heat interaction is based on the temperature difference on both sides of the interface.
[0104] Furthermore, a grid is set for the constructed three-dimensional geometric parts. Since it is a rectangular thin-walled model, a triangular distributed grid can be selected to reduce the amount of calculation while ensuring the accuracy of the simulation results. The grid can be refined at the corners and vertices of the model. The grid division effect is as follows: Figure 2 shown.
[0105] Furthermore, after setting various parameters in the finite element simulation software, a steady-state solution of the model is performed. By reading information files such as the heat transfer coefficient, thermal conductivity and heat transfer path of the set material and combining it with the calculation of thermodynamic formulas, the real-time changes in temperature, response speed and energy density at various locations of the phase change material model can be obtained. The simulation results are compared with the actual test results, and the error rate below 5% proves the reliability of this test.
[0106] Finally, the response speed and energy density parameters obtained in each test are marked at the corresponding points in the Ragon diagram to obtain the trade-off relationship between energy density and response speed in the phase change material system.
[0107] The above steps are used to test the temperature change and total test time of the graphite wax composite phase change material at three different heating powers and cut-off temperatures. Then, according to the derived formula, the Lagun diagram of the energy density and response speed of the sample at different heating powers is calculated, as shown in Figure 3 As shown in , under the premise that the sample energy density remains unchanged, as the cut-off temperature increases, the fastest response speed that can be achieved becomes higher.
[0108] Furthermore, the finite element simulation model of the graphite paraffin composite phase change material is analyzed by software, and the real-time phase change during the test process is as follows: Figure 4 As shown in the figure, it can be clearly observed that as the test experiment proceeds, more and more solid areas melt into liquid areas, and the interface between the solid and liquid is stepped. On the other hand, the part closer to the heat transfer fluid has a higher temperature at the same time, and the temperature decreases from near to far. The finite element simulation clearly shows the phenomenon that is difficult to observe in the actual test. At the same time, the results of the actual test and calculation are fitted with the results of the finite element simulation. The fitting effect is shown in the figure. Figure 5 As shown, under three different heating powers, the actual test results are very close to the finite element simulation results, and the error is less than 5%, which strongly proves that the test results of this sample are accurate and reliable.
[0109] Embodiment 2
[0110] Pure tetradecane, pure ammonium bromide, graphite paraffin composite material, graphene paraffin composite material and aluminum alloy paraffin composite material were selected as test objects. These different system materials were made into rectangular samples of specified sizes. The sample surface area was large and the thickness was thin. At the same time, the basic information of the tested samples, such as mass, density, porosity and processing technology, was recorded. The complete test steps are as follows: Figure 1 shown.
[0111] The samples to be tested are tested in a constant temperature and heat preservation environment. Starting from the same initial temperature, different heating powers are used to heat the samples through the heat transfer medium. At the same time, different heating powers correspond to different cut-off temperatures. The temperature changes of the samples to be tested under different heating powers and the time to heat up to the cut-off temperature are recorded.
[0112] The subsequent calculation derivation process and finite element simulation process of this embodiment are as described in the first embodiment. Finally, the trade-off relationship between energy density and response speed in each phase change material system can be obtained, such as Figure 6 As shown, pure phase change materials can only achieve lower energy density and response speed than composite phase change materials, while the composite phase change material system using metal materials as an auxiliary thermal conductive framework can show a higher response speed. These performance comparison results can provide a reference for the future improvement and optimization of phase change material systems.
[0113] The above description is only a description of the preferred embodiment of the present invention, and is not any limitation on the scope of rights of the present invention. Any person skilled in the art can make possible replacements, changes and modifications to the technical solution of the present invention by using the methods, components and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for characterizing the energy density and response speed of phase change energy storage composite materials. It is characterized in that The steps include: Step 1: The phase change material or composite phase change material to be tested is made into a standard sample, and an experimental test is carried out under uniform test conditions to obtain the temperature change curve and total heating time of the material sample; Step 2: Based on the phase change temperature range of the phase change material and the relevant data obtained from the test, according to the working principle of the heat engine and the laws of thermodynamics, the thermal physical property parameters of the phase change material sample are calculated; Step 3: Establish the thermomechanical coupling relationship between temperature field and solid-liquid phase change and the finite element model for heat transfer calculation, submit the simulation conditions for multi-physics field coupling, and complete the subsequent solution, post-processing and result analysis of the finite element; Step 4: Obtain the energy density and response speed of the phase change material sample based on calculation and finite element simulation. On the basis of repeating steps 1 to 3, obtain the energy density corresponding to different response speeds. Use the large amount of data obtained to make a Lagun diagram to compare the trade-off between energy density and response speed of each phase change material system.
2. According to step 1 of claim 1, It is characterized in that The phase change material is made into a rectangular sample of specified size with a large surface area and thin thickness. At the same time, basic information such as the mass, density, porosity and processing technology of the sample is recorded. The sample is tested in a constant temperature and insulation environment and at the same initial temperature. Different heating powers are used to heat the sample through a heat transfer medium. At the same time, different heating powers correspond to different cut-off temperatures. The temperature changes of the sample under different heating powers and the time to heat up to the cut-off temperature are recorded.
3. According to step 2 of claim 1, It is characterized in that According to the working principle of heat engine and the derivation of thermodynamic formula, when the heat transfer medium is in contact with high temperature (heat source) and low temperature (sample) substances at the same time, the law formula 1 and public statement 2 are satisfied: Formula 1: Formula 2: Among them, T H is the instantaneous maximum temperature of the heat transfer medium after being heated by the heat source, T L It is the instantaneous minimum temperature of the heat transfer medium after it absorbs heat from the sample being tested and before it is heated again. HC is the instantaneous temperature of the heat transfer medium when it contacts the sample being tested, T LC Q is the instantaneous temperature when the heat transfer medium and the sample are about to separate. HC Q is the heat carried by the heat transfer medium from the heat source to the sample under test. LC It is the heat carried by the heat transfer medium from the separation of the sample to the reheating process, α is the heat transfer coefficient, n is the heat transfer index, and t is the duration of the whole process.
4. According to step 2 of claim 1, It is characterized in that According to the definition of energy density and response speed, the thermophysical parameters of the tested sample are derived to obtain Formula 6, Formula 7, Formula 8 and Formula 9: Formula 6: Formula 7: Formula 8: Formula 9: Among them, P is the heat transfer power, which is also one of the characterization methods of response speed. η is the capacity utilization efficiency, which represents the utilization rate of the heat that the measured sample can absorb at this response speed relative to the theoretical total heat storage. E is the total energy storage that the measured sample can achieve at this response speed. Es is the energy density related to mass, and m is the mass of the measured sample.
5. According to step 2 of claim 1, It is characterized in that Furthermore, the optimal value of heat transfer power that satisfies both fast response speed and high energy density can be obtained. The optimal value means that within a unit time, the phase change energy storage response can be completed quickly, and at the same time, the energy density achieved at this response speed is the highest compared to the same level, which is the best performance in balancing response speed and energy density. The optimal response speed P max , maximum efficiency η max , optimal total energy E max and the optimal energy density Es max , as shown in the derivation of Formula 17, Formula 18, Formula 19 and Formula 20: Formula 17: Formula 18: Formula 19: Formula 20:
6. According to step 3 of claim 1, It is characterized in that Since it is a rectangular thin-walled model, a triangular distributed grid can be used to reduce the amount of calculation while ensuring the accuracy of the simulation results. The grid can be refined at the corners and vertices of the model. After setting the various parameters in the finite element simulation software, the steady-state solution of the model is performed. The simulation results can be compared with the actual test results. If the error rate is below 5%, it proves the reliability of this phase change material sample test.
7. According to step 4 of claim 1, It is characterized in that The same phase change material sample can be tested repeatedly for multiple times to test the energy density that the sample can achieve at different response speeds. Different response speeds can be set with a value range and a step-by-step value to reduce the overall testing workload. The response speed and energy density parameters obtained in each test are marked at the corresponding points in the Lagun diagram to obtain the trade-off relationship between energy density and response speed in the phase change material system.
8. Characterizing the energy density and response speed of phase change materials according to any method or step of claims 1 to 7 does not deviate from the content of the technical solution of the present invention. Any simple modification, equivalent change and modification based on the technical essence of the present invention falls within the protection scope of the solution of the present invention.
Citation Information
Cited By
Equipment and method for testing heat storage performance of phase change heat storage refractory material
CN121955079A
